The Effect of Self Efficacy and Work Environment on Employee Performance of PT. XYZ - Mohamad Yusuf Fachriwan; Muhamad Alwi; Dharliana Hardjowikarto (Interdisciplinary Social Studies, 2026)
Employee performance is critical to organizational success. PT. XYZ, a Pertamina lubricant distributor in Cirebon, faces challenges in achieving consistent sales targets and operational stability, highlighting the need to understand factors influencing performance, particularly self-efficacy and work environment. This research aims to examine the influence of self-efficacy and the work environment, both partially and simultaneously, on the performance of employees of PT. XYZ. The study employed a quantitative approach with an associative design. The population consisted of all 54 employees of PT. XYZ, and the saturated sampling technique was used, meaning the entire population served as the sample. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 25. The analysis included validity and reliability tests, classical assumption tests, partial significance tests (t-test), simultaneous significance tests (F-test), and the coefficient of determination. The results show that self-efficacy positively and significantly affects employee performance (t-count = 7.187 > t-table = 1.674, p < 0.05). The work environment also has a positive and significant effect (t-count = 8.108 > t-table = 1.674, p < 0.05). Simultaneously, both variables significantly influence employee performance (F-count = 77.651 > F-table = 3.18, p < 0.05), with an adjusted R² of 0.743, indicating that 74.3% of the variation in performance is explained by both factors. Self-efficacy and the work environment positively and significantly influence employee performance at PT. XYZ, both partially and simultaneously. Strengthening employee confidence and creating a supportive work environment are essential strategies for enhancing organizational performance.